Investigation of Insulation Effect on Wax Deposition Using a Flow Assurance Simulator - Astra Agus Pramana; Inggrialianthari Rezkhi Trinugrahandini (Testing Center for Oil and Gas LEMIGAS, 2026)
Wax deposition remains one of the most common and disruptive problems in oil and gas pipelines. To address this issue, various methods are developed for both onshore and offshore fields according to their field characteristics. Insulation is one of the mitigation methods that generally performs well, despite several implementation challenges. This study presents a wax-deposition model to assess the effectiveness of insulation as a mitigation method. The analyzed fluid flows from the MOON platform to the SELENA platform in Field W through a carbon-steel subsea pipeline. The pipeline is modeled over a simulated distance of approximately 0–1,900 m, with detailed wax-deposition analysis focused on the critical section of 0–700 m. Rubber and concrete are applied to evaluate their performance as pipeline insulation materials. This study uses five scenarios with two different materials. The results show that, in all cases, wax thickness reduction reaches 100%, while rubber insulation performs more effectively than concrete in reducing temperature decline and heat loss. In addition, other parameters, such as pressure, Wax Appearance Temperature (WAT), and flow rate, are analyzed in this study.